(untitled) (Bangladesh Journal of Zoology, 2023)
The northwest regions of Bangladesh belong to the global range of Bengal fox, Vulpes bengalensis. However, scientific information on this small canid in Bangladesh is scanty; it also remains out of any conservation initiatives, and it is widely perceived as a potential threat to local poultry. We conducted this premier study between September 2019 and December 2021. We investigated the feeding and breeding behaviour of this fox by using scat samples, direct field surveys and camera-trapping. An analysis of 67 scats yielded eight major categories of prey items consumed by the fox. Arthropods (29%) ranked top in the relative percentage of occurrence, followed by rodents (27%), plant parts (17%), and birds (13%), among the others. Ninety-two percent of scats contained multiple food items, with an average number of food items per scat of 3.50± SE 1.87. We recorded 17 den sites in and around human-dominated landscapes, of which nine den sites remained unoccupied during the entire study period. Dens used by Bengal foxes were complex, comprising interconnected tunnels and holes with an average of 23.66± SD 12.78 holes/den. We estimated a total of 37 individuals of the fox, with 62% pups in the recorded population. The average litter size was 3.36± SE 0.52 pups. We recommend further research to assess population status and delineate its range in Bangladesh. Bangladesh J. Zool. 51(1): 35-45, 2023